The impact of project-based learning on enhancing students’ mathematical communication skills - Mustika, Helma; Ningsih, Sri Yunita; Wahyuni, Wahyuni (Mahesa Research Center, 2025)
This study investigates the impact of the Project-Based Learning (PBL) model on the mathematical communication skills of eighth-grade students at SMP Negeri 3 Sungai Lala. The research was motivated by the need to improve students' ability to articulate mathematical ideas clearly and accurately, a skill often found lacking in conventional classroom settings. Adopting a quasi-experimental design with a posttest-only control group, two classes were selected: one as the experimental group receiving PBL instruction, and the other as the control group receiving conventional teaching methods. The PBL approach was implemented by engaging students in structured projects that required collaborative problem-solving, critical thinking, and the presentation of mathematical concepts in both oral and written forms. Data were collected through a standardized mathematical communication skills test designed to assess clarity of explanation, accuracy of reasoning, and the effective use of mathematical representations. Statistical analysis using the Independent Samples t-test revealed a significant difference in performance between the two groups (p < 0.05). Students exposed to the PBL model achieved notably higher scores, indicating superior proficiency in expressing and justifying mathematical ideas compared to their peers in the conventional group. These findings highlight the potential of PBL as an alternative instructional strategy to enhance mathematical communication skills, aligning with current educational goals that emphasize active learning and the development of 21st-century competencies. The study recommends broader application of PBL in mathematics education, particularly in contexts where fostering communication and reasoning is a priority.